A Highly Transparent Self-Powered Touch Sensor Based on Hierarchical (Micro-Nano) Cu Grid on Polyethylene Terephthalate Composite Electrodes for Smart Wear - Cao, Weiqi; Shaker, Majid; Lei, Wenqian; Yu, Hua (Journal of Materials Engineering and Performance, 2023)
With the expansion of the applications of sensors, requirements such as flexibility, visual transparency, and self-powering have become critical. In this work, firstly we have adopted photoetch and hierarchical (micro-nano) manufacturing techniques to fabricate a micro-scale copper grid on polyethylene terephthalate (PET). This material (Cu grid @PET) exhibits high transmittance (89% at 550 nm, only 2.7% lower than PET substrate) and low electric resistance (6.7 Ω sq−1) compared with other reports. Then, the as-fabricated Cu grid @PET composite electrode, poly-dimethylsiloxane (PDMS), and polymethyl methacrylate (PMMA) were utilized to fabricate a sandwich-like structured transparent self-powered sensor (TSPFS) with high optical transmittance of 85.5-87.5% (450 620 nm). A complete novel control method combining with sensor’s electrical signal test was implemented by Dynamic Mechanical Analyzer (DMA), verifying the simulation response to space of COMSOL. Voltage signals could be also observed when the sensor was touched by fingers without receiving electric energy from external sources. Finally, the paper shows a kind of smart goggles made of the produced transparent device, exhibiting heating, antifogging, and sensing functions.
CRIS-Team Scopus Importer:2023-03-03
Keywords: coating; laser photoetching; smart wear; transparent and flexible electrode; zero-energy sensor